85.7k views
5 votes
3h - 2(4h - 5) = 10 - 5h A 0 B 4 C infinity many solutions D no solutions

User Pptang
by
4.9k points

1 Answer

7 votes

ANSWER

D. No solutions

Step-by-step explanation

We have to simplify the equation given:

3h - 2(4h - 5) = 10 - 5h

We have to expand the bracket first:

3h - 8h + 10 = 10 - 5h

Now, collect like terms:

3h - 8h + 5h = 10 - 10

=> 0 = 0

We can safely conclude that this equation has no solutions for this equations are there are no possible values for h.

In other words, it is undefined.

User Chris Charles
by
5.4k points